1991
DOI: 10.1111/j.1469-8986.1991.tb03388.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Measures of Sleepiness: Effect of Benzodiazepine and Caffeine on Their Relationship

Abstract: As part of a larger project on the effects of benzodiazepine and caffeine on daytime sleepiness, performance and mood, this study examined the relationship among the Multiple Sleep Latency Test, lapses during a tapping task, a Visual Analog Scale, and the Stanford Sleepiness scale. Subjects were 80 male, adult nonsmokers aged 20.3 +/- 2.7 years. The Multiple Sleep Latency Test, Stanford Sleepiness Scale, and the Visual Analog Scale were obtained at two-hour intervals beginning at 0700 h and ending at 1700 h. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
4

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 24 publications
(13 reference statements)
3
17
0
4
Order By: Relevance
“…3). This ®nding is similar to that of Johnson et al (1991), who have demonstrated a discrepancy between the Multiple Sleep Latency Test (MSLT) score and parameters of subjective sleepiness. Further study will be needed to clarify the underlying mechanisms of such a dissociation.…”
Section: Discussionsupporting
confidence: 73%
“…3). This ®nding is similar to that of Johnson et al (1991), who have demonstrated a discrepancy between the Multiple Sleep Latency Test (MSLT) score and parameters of subjective sleepiness. Further study will be needed to clarify the underlying mechanisms of such a dissociation.…”
Section: Discussionsupporting
confidence: 73%
“…In this regard, it is important to mention that physiological sleepiness can often not be reliably assessed by introspection. Sleep propensity as measured by the sleep latency tests and subjective sleepiness are often uncorrelated and may measure different aspects of sleepiness (Johnson et al 1991;Moldofsky 1992;Johns 1994). Moreover, subjective assessments may be insensitive especially when the "sedation" is excessive or has been present persistently (Roth et al 1989).…”
Section: Discussionmentioning
confidence: 98%
“…Caffeine has been repeatedly shown to attenuate performance impairments due to decreases in arousal induced by sleep loss, fatigue, working at night, or by sedative drugs [89][90][91][92][93]. Furthermore, caffeine can remove the impaired performance and negative mood associated with the common cold [94] and attenuate memory impairment induced by scopolamine in humans [95].…”
Section: S243mentioning
confidence: 99%